2004
DOI: 10.1191/1358863x04vm525oa
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers, D-dimer, pro-thrombotic factors, and physical activity levels in patients with peripheral arterial disease

Abstract: Men and women with lower extremity peripheral arterial disease (PAD) have reduced physical activity levels compared with persons without PAD. We describe associations between physical activity levels with D-dimer, pro-coagulant factors, and inflammatory markers in patients with PAD. Participants were188 patients with PAD identified from non-invasive vascular laboratories. Physical activity was measured over 7 days with a vertical accelerometer. We measured the ankleÀbrachial index (ABI) and levels of D-dimer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…10 Thus, it has been suggested that ACE inhibitors may favorably modify inflammation and thrombosis, both of which are critical in the complications of atherosclerosis [11][12][13] and functional decline in patients with PAD. 14 In the current study, we conducted exploratory analyses of the potential mechanisms underlying the improvement in functional capacity observed after ramipril therapy, through the assessment of circulating biomarkers related to angiogenesis/arteriogenesis, inflammation, leukocyte adhesion, and thrombosis.…”
Section: Ahimastos Et Al Ramipril and Intermittent Claudication 1145mentioning
confidence: 99%
“…10 Thus, it has been suggested that ACE inhibitors may favorably modify inflammation and thrombosis, both of which are critical in the complications of atherosclerosis [11][12][13] and functional decline in patients with PAD. 14 In the current study, we conducted exploratory analyses of the potential mechanisms underlying the improvement in functional capacity observed after ramipril therapy, through the assessment of circulating biomarkers related to angiogenesis/arteriogenesis, inflammation, leukocyte adhesion, and thrombosis.…”
Section: Ahimastos Et Al Ramipril and Intermittent Claudication 1145mentioning
confidence: 99%
“…Fourth, increased levels of physical activity could favorably alter gait, resulting in more efficient walking techniques 46,47. Finally, higher physical activity levels are inversely associated with inflammatory markers in PAD persons 48. These physiologic and metabolic changes associated with physical activity may explain the association of higher physical activity with slower functional decline among persons with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, participants with the highest D-dimer and IL-6 levels had the greatest decline in ABI over a 12-year period 88. McDermott et al have demonstrated an elevated D-dimer to be associated with walking impairment,41 functional capacity,39 physical activity levels,40 and functional decline over time 42. Whether D-dimer is involved in the pathophysiology of functional impairment in PAD patients or is simply a marker of the same is not established 38.…”
Section: Thrombosismentioning
confidence: 99%